2000
DOI: 10.1029/1999jd900921
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of TOVS‐derived land surface variables with ground observations

Abstract: Abstract. The Tiros Operational Vertical Sounder (TOVS) Pathfinder Path A retrieved surface skin temperature, surface air temperatures, and surface specific humidity are compared with data obtained from three large-scale field campaigns: the First ISLSCP (International Satellite Land Surface Climatology Project) Field Experiment (FIFE), the Hydrologic Atmospheric Pilot Experiment (HAPEX) in the Sahel, and the Boreal Ecosystem-Atmosphere Study (BOREAS). The long-term estimates of surface skin temperatures, surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Susskind et al (1997) have shown that the TOVS Path nder Path A dataset, in which the satellite observations are used in a data assimilation mode within a GCM, provide reasonable estimates of surface air temperature globally. Lakshmi et al (1997Lakshmi et al ( , 1998Lakshmi et al ( , 1999 have validated these temperatures using observations from eld experiments and meteorological observing stations and have shown them to be unbiased. Secondly, an innovative approach that uses multi-afternoon Advanced Very High Resolution Radiometer (AVHRR) surface skin temperature and Normalized DiOE erence Vegetation Index (NDVI) to estimate air temperature has been developed and implemented (Goward et al 1994).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Susskind et al (1997) have shown that the TOVS Path nder Path A dataset, in which the satellite observations are used in a data assimilation mode within a GCM, provide reasonable estimates of surface air temperature globally. Lakshmi et al (1997Lakshmi et al ( , 1998Lakshmi et al ( , 1999 have validated these temperatures using observations from eld experiments and meteorological observing stations and have shown them to be unbiased. Secondly, an innovative approach that uses multi-afternoon Advanced Very High Resolution Radiometer (AVHRR) surface skin temperature and Normalized DiOE erence Vegetation Index (NDVI) to estimate air temperature has been developed and implemented (Goward et al 1994).…”
Section: Introductionmentioning
confidence: 82%
“…provide four times of day observations and are useful in assessing diurnal dynamics of the land surface. Direct comparisons between eld observations collected during FIFE (First ISLSCP (International Satellite Land Surface Climatology Project) Field Experiment) and the TOVS-derived skin and surface air temperature and surface vapour pressure for a period between 1987 and 1989, between observations from the HAPEX (Hydrologic-Atmospheric Pilot Experiment) Sahel and between the observations from the Boreal Ecosystem Atmosphere Study (BOEAS), 1993-1996 and the same TOVS parameters (as mentioned above), have been carried out (Lakshmi et al 1999). The standard deviation of the diOE erences between the instantaneous satellite retrieved quantities and the ground data obtained in the eld experiments for surface skin temperature, surface air temperature and surface vapour pressure were found to be 4ß C, 3.5ß C and 3.5 mb, respectively, and nearly zero mean biases over the experiment periods.…”
Section: T Ovsmentioning
confidence: 99%
“…In order to understand the relationship between soil moisture and surface temperature, field studies must be conducted to obtain accurate and reliable (simultaneous in time and coincident in space) soil moisture and surface temperature observations. Field measurements of surface temperature have been used for validation of satellite-retrieved surface temperatures (Lakshmi et al, 1998;Prince et al, 1998;Lakshmi and Susskind, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The skin temperature is derived using the infrared-thermal channel 8, 18, and 19 of the High-Resolution Infrared Radiation Sounder instrument. The dataset (Susskind et al 1997) has been validated (Lakshmi et al 1998;Lakshmi and Susskind 2000) for various land surface regions by direct comparison to surface temperature collected during field ex- periments. The results of these comparisons are that the two datasets (TOVS and in situ) have approximately zero mean difference.…”
Section: A Skin Temperaturementioning
confidence: 99%